Análisis comparativo de contenidos audiovisuales entre netflix y la television por cable y su recepción social en los estudiantes del 8vo semestre Comunicación Social de la Universidad Técnica de Babahoyo Ext- Quevedo - Jimenez Castellano, Julissa Azucena (2021)
This Final Degree Project is analyzed through a study on the growth of Netflix, which is a company that provides a video-on-demand service and is available in more than 190 countries. A diagnosis of the situation is established to identify the competitive advantage of the Netflix and cable television company. Netflix follows an internal and external analysis in which a diagnosis of the situation is carried out and also studies a competitive advantage of both companies. To develop this research and measure the satisfaction perceived by the client, it has been taken as the main objective to carefully analyze each of its study processes and propose improvements for an adequate level of client satisfaction, it was necessary to apply some methods and techniques in order to For the research to have key foundations to support said study, it was necessary to apply indicators to properly analyze whether customers were feeling satisfied with the service they receive from the company, with the sole purpose of making the customer feel like the person More importantly, within this research, techniques such as the survey have been used, which provide greater emphasis on research since it is the starting point for development, in such a way that these are the events that the research throws up made to clients of the cable television company and Netflix.